Human Computer Interface for Wheelchair Movement - Baghdad Science Journal (مجلة بغداد للعلوم)
This paper aims to develop a technique for helping disabled people elderly with physical disability, such as those who are unable to move hands and cannot speak howover, by using a computer vision; real time video and interaction between human and computer where these combinations provide a promising solution to assist the disabled people. The main objective of the work is to design a project as a wheelchair which contains two wheel drives. This project is based on real time video for detecting and tracking human face. The proposed design is multi speed based on pulse width modulation(PWM), technique. This project is a fast response to detect and track face direction with four operations movement (left, right, forward and stop). These operations are based on a code written in MATLAB environment and Arduino IDE environment. The proposed system uses an ATmega328microcontroller (Arduino UNO board).